Health Innovation In Kemranggon Hamlet, Tanjung Kulon Village, Kajen District, Pekalongan: Boiled Bay Leaves - Endriyatno, Nur Cholis; Walid, Muhammad; Priagung, Andri; Diva, Rihadatul (Kontribusia : Research Dissemination for Community Development, 2024)
In Indonesia, the prevalence of hypercholesterolemia continues to increase, where at the age of 25 - 34 years the prevalence of this disease is 9.30%, and for those aged more than 55 years to those aged less than 65 years 15.50%. To overcome the problem of hypercholesterolemia, there are various types of antihypercholesterolemic synthetic drugs, but sometimes these drugs have certain side effects. Therefore other alternatives that come from nature are needed. Bay leaves contain flavonoid compounds. This compound can lower cholesterol levels. Bay leaves boiled and brewed in the morning and evening have been proven to reduce cholesterol levels. From this background, providing community service regarding bay leaf drinks is necessary to help lower cholesterol levels. The bay leaf drink preparation was chosen because of its ease and acceptability which is easily applied by the public. The target of this service is Kemranggon Hamlet, Tanjung Kulon Village, Kajen District, Pekalongan. The service method used is participatory action research (PAR). This community service increases public understanding regarding making boiled bay leaf to help lower cholesterol. This can be concluded by increasing pretest and posttest scores.